Hiding in plain sight: Private military and security companies' use of Twitter as a distraction tool. (December 2019) - Schneiker, Andrea; Dau, Magnus; Joachim, Jutta; Martin, Marlen; Lange, Henriette
Private military and security companies (PMSCs) have an image problem. They are frequently called 'mercenaries' or 'dogs of war', due to recurring scandals involving some of these companies, such as human rights violations, fraud and waste. Scholars have analysed the strategies that PMSCs use to distance themselves from such negative labels and to boost their image by studying the companies' websites and advertisements. What is missing so far, however, is an analysis of how PMSCs use social media networking sites in order to present themselves in a positive light. In this article, the authors contribute to filling this gap. Based on assumptions generated with the help of literature on PMSCs, on the one hand, and on business communication and social media, on the other, they analysed the Twitter accounts of 58 PMSCs by using both quantitative and qualitative methods. Their findings suggest that PMSCs use Twitter similar to more generic companies: (1) to promote their own services and products, and (2) to monitor what others say about them. However, Twitter also serves a further purpose for PMSCs not acknowledged thus far. It helps to distract from what these companies are actually doing. Rather than engaging in more or less similar strategies as the literature on corporations' social media use conveys, the functions of different platforms appear to vary across industries. In the case of PMSCs, their particular use of Twitter can be attributed to the sensitive nature of the security services they provide.